2017
DOI: 10.1002/jsfa.8205
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' expectations and acceptability for low saturated fat ‘salami’: healthiness or taste?

Abstract: The present study highlights that nutritional information is not enough to satisfy consumers' expectations if the product is not sensorily acceptable. Findings about the relevance of information and consumers' segmentation could have important implications for policy makers and the meat product industry. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In addition, consumers may not formulate or carry out strategies to change their patterns of purchase and consumption of dietary products, because they value established preferences and feel that individual acts of consumption will not affect their health. 37 This finding is in line with many previous studies (eg, [59][60][61] which have shown that nutritional information is not the sole influence on individuals' choices or intentions to purchase a product. However, it remains necessary to investigate the reasons behind this low impact on consumers' decisions in an e-commerce platform.…”
Section: Resultssupporting
confidence: 89%
“…In addition, consumers may not formulate or carry out strategies to change their patterns of purchase and consumption of dietary products, because they value established preferences and feel that individual acts of consumption will not affect their health. 37 This finding is in line with many previous studies (eg, [59][60][61] which have shown that nutritional information is not the sole influence on individuals' choices or intentions to purchase a product. However, it remains necessary to investigate the reasons behind this low impact on consumers' decisions in an e-commerce platform.…”
Section: Resultssupporting
confidence: 89%
“…The sensory features of the product also play a role in its perceived healthiness. The taste and other sensory features of the product may dominate over the perception of healthiness [ 41 , 52 , 79 ], and if the sensory features of the product do not satisfy the consumer, then communicating the nutritional value is not enough to make the product accepted [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sensorial attributes are likely to gain further importance in that taste is a major determinant of consumption choice in the food industry (Miller et al, 2001). In addition, changes in consumer acceptability for new preparations are likely to lead to the development of new products (Marino et al, 2017). Future opportunities for producers are based on the high segmentation of the market for meat products, and on the potential strategies of differentiation that may be implemented in order to meet the public interest toward sustainability issues, environmental efficiency, impact of carbon footprint, animal welfare and healthiness (Kristensen et al, 2014).…”
Section: Figure 1 About Herementioning
confidence: 99%